A very long-term observation of a family with dilated cardiomyopathy and overlapping phenotype from lamin A/C mutation. Issue 1 (January 2021) - Porcu, Maurizio; Corda, Marco; Pasqualucci, Daniele; Binaghi, Giulio; Sanna, Nadia; Matta, Gildo; Cossa, Stefano; Scalone, Antonio; Tola, Gianfranco
Abstract : Aims: We aim to describe one of the longest longitudinal follow-ups reported so far (>22 years), concerning a whole family affected by a missense lamin A/C mutation (Arg60Gly), which manifested as an overlapping phenotype with cardiac and extracardiac involvement over time. Methods: Starting from the family history, two generations of that family were prospectively observed, from 1997 until 2020. At baseline, four individuals with dilated cardiomyopathy and cardiac conduction defects showed the same mutation. This was also found in three young individuals, phenotypically unaffected at baseline assessment. Results: The prolonged clinical and laboratory evaluation has shown the evolution of an overlapping phenotype in which cardiac alterations have been associated with lipodystrophy and neurological manifestations. In the first observed generation, the prognosis was negatively affected by the progression of heart failure and lipodystrophy, whereas in the second generation the first phenotypic manifestations became evident after the 2nd decade. Cardiac magnetic resonance played a relevant role in the early detection of cardiac alteration. Right bundle branch block was another sign of initial phenotypical expression. Conclusion: In lamin A/C gene mutation carriers, a strict, multidisciplinary follow-up allows the opportunity to monitor the progress of the disease and to intervene precociously with the best available treatments.